INCREASING VALUE IN THE COURT SYSTEM OPERATION – A CASE STUDY - Martins, A.; Crespo de Carvalho, J. (XXIV jornadas luso-espanholas de gestão científica, 2014)
Courts of Law are widely criticized not for the quality of their decisions but for how long they take to produce and make final decisions available. It is often that once results are available they are no longer relevant, which translates waste in the use of resources. This paper aims at identifying why the flow of legal cases does not produce more value to its final customers and explore ways to make it increase the value provided. Research will be based on a logistics approach and process synchronization. Two case studies are compared, and a random and representative sample of 299 civil summary cases is used. Court cases are analysed both from the perspective of the activities in the legal process and the resources that are used in that process. Statistical analysis is used. Findings show that delays of court cases occurs mainly due to direct human intervention, particularly from the judge the case was assigned to and his staff. Recommendations to improve customer value are provided.